Co-Production of Public Space:: Redefinition of Social Meaning Through Participative Laboratories - COWDROY, Rob; MICHIALINO, Paola (ARCC Conference Repository, 2019)
This paper provides an outline of particular aspects of a research project evaluating the pilot development and trial of a new strategy using participative laboratories in an integrated process for the design of public space in France. The participative laboratory strategy was trialed in five projects realised with the support of the State and of the Region Nord – Pas de Calais. The context of the present study was a series of pilot participative laboratories developed by the research team Habitat and Development (H&D), based at the Catholic University of Louvain (UCL), Belgium. The projects related to the present study were at Avion, Haubourdin Centre, Haubourdin Petit Belgique, Saint Pol sur Mer, and Tourcoing. Other laboratories initiated at Bruay-la-Buissière and the Communauté de Communes du Val de Sambre were only partially completed, and are not included in the present study. A further laboratory, Saint-Josse-ten-Noode in Belgium, will offer comparisons with a laboratory in a different political and administrative system. The pilot participative laboratories included in the present study involved politicians, bureaucrats, professional experts and lay citizens in multi-cultural and multi-disciplinary discussion-based design processes, and expanded the agenda of the design process beyond technical and logistics considerations to include local social, cultural and lifestyle issues. The purpose of the present study was to evaluate the impact of the new strategies on development of social meaning of public spaces and of the design process itself. This paper focuses on the innovative process of participative laboratories and its contribution to achievement of development of social meaning. This paper focuses the proposed theme 2: research results concerning design and culture: architecture as a medium of cultural identity.